Supervisi Observasi Kelas untuk Meningkatkan Kinerja Guru pada MI Hayatul Ulum Pangean Maduran Lamongan - Juri Wahananto (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The purpose of this study is to improve the ability of the madrasa principal in supervising class observations of teachers in relation to efforts to improve teacher performance, and to improve teacher performance in the learning process when supervised by madrasah principals through classroom observation supervision techniques. The method used in this research is descriptive. qualitative research, the type of research that will be used is qualitative research. this type of research will be designed using Madrasah Action Research (PTM) or School Action Research (SAR). Action research has characteristics that are participatory, involving program implementers to be improved. The results of supervision on teacher teaching abilities in cycle I-cycle III obtained the following averages: Ability to manage class, time, and learning facilities 3.5, Ability to use learning strategies 3.22, Ability to manage class interaction 3.48, Ability to help develop positive attitudes of students towards learning 4.1, Ability to carry out evaluation of learning processes and outcomes 4.36, Teacher's teaching ability in each cycle are as follows: cycle 1: 3.20, cycle 2: 3.68 and cycle 3: 4.31.